Practical SharePoint 2010 Information Architecture - Gotz, Ruven. (Apress : Imprint: Apress, 2012)
Practical SharePoint 2010 Information Architecture is a guide and tool set for planning and documenting the scope, navigational taxonomy, document taxonomy, metadata, page layouts and workflows for a successful SharePoint 2010 project. If you have been tasked with delivering an intranet for collaboration, document management or as a corporate portal, your only chance for success is to get all of these elements right, and then to make sure that you and your stakeholders are all on the same page. SharePoint 2010 can be dangerous to your career: Expectations are often set very high, and not enough time is invested in understanding how those expectations can be met. Many SharePoint 2010 projects fail to meet their initial goals. Practical SharePoint 2010 Information Architecture arms you with proven tools that will help you to ensure that there is an agreement on the goals and scope, and how to then efficiently design your taxonomies. With author Ruven Gotz' work (with contributions from Michal Pisarek and Sarah Haase) at your side, You will learn how to educate your users on what metadata is and why it is important so you can build SharePoint 2010 solutions that exceed the expectations of your users. This book: Gives you practical approaches that have been proven in the field Explains how to use visual mind mapping tools and diagramming tools that provide clarity to all stakeholders Gives you techniques on how to teach and motivate your users for adoption and success.